Power of Translation of QS. Al-Mâ’idah 51 on the Conservative Islamic Website in Indonesia - Waki Ats Tsaqofi; Akhmad Saehudin; Sarah Hajar Mahmudah (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2023)
This article aims to discover the translation of the word auliyâ’ in QS. Al-Mâ’idah Verse 51 on a conservative Islamic website in Indonesia. In addition, to find out the power and discursive practice of the verse and uncover ideology in social practice. The study was qualitative research that used the text published on Portal-islam.id and Voa-islam.com as the primary source. In data analysis, the study applied Norman Fairclough’s critical discourse analysis. The study showed that Portal-islam.id and Voa-islam.com translated the word auliyâ’ as leaders. That is motivated by Hamka’s interpretation which prioritizes meaning compared to the reason for the revelation of the verse. For this understanding, conservative Islamic websites produce articles that support the prohibition of non-Muslims from becoming leaders.